Research and application of device for simulation sports training based on cycle condition - Zhao, J. (MATEC Web of Conferences, 2017)
The slope simulation method of the spiral mechanism, the rubbing transmission, the resistance simulation method of magnetic particle brake loading on the rear wheel is proposed by anglicizing the road sports conditions and resistance of the actual cycling. the structure design, loading design and control design of the road sports condition simulator is designed. the structure of putting the motor forward and forcing the big sprocket rotation through the chain transmission, and the method of the frequency converter regulates the rotational speed of the motor within the range of certain frequency, PLC programming the rotation rules is adopted. The complete device is applied to athletes sports training of the national bicycle team at ordinary times after debugging successfully.